Improved method for genotyping the causative agent of crayfish plague (Aphanomyces astaci) based on mitochondrial DNA. Issue 8 (12th April 2019) - Minardi, Diana; Studholme, David J.; Oidtmann, Birgit; Pretto, Tobia; van der Giezen, Mark
Abstract: Aphanomyces astaci causes crayfish plague, which is a devastating disease of European freshwater crayfish. The likely first introduction of A. astaci into Europe was in the mid-19th century in Italy, presumably with the introduction of North American crayfish. These crayfish can carry A. astaci in their cuticle as a benign infection. A phanomyces astaci rapidly spread across Europe causing the decline of the highly susceptible indigenous crayfish species. Random amplified polymorphic DNA-PCR analysis of A. astaci pure cultures characterized five genotype groups (A, B, C, D and E). Current A. astaci genotyping techniques (microsatellites and genotype-specific regions, both targeting nuclear DNA) can be applied directly to DNA extracted from infected cuticles but require high infection levels. Therefore, they are not suitable for genotyping benign infections in North American crayfish (carriers). In the present study, we combine bioinformatics and molecular biology techniques to develop A. astaci genotyping molecular markers that target the mitochondrial DNA, increasing the sensitivity of the genotyping tools. The assays were validated on DNA extracts of A. astaci pure cultures, crayfish tissue extractions from crayfish plague outbreaks and tissue extractions from North American carriers. We demonstrate the presence of A. astaci genotype groups A and B in UK waters.